ANALYSIS OF THE APPLICATION OF PANCASILA IN THE INFORMATICS CLASS STUDENTS OF MEDAN INSTITUTE IN DAILY LIFE - A. Zebar (Universitas Negeri Medan, 2018)
Abstract : Analysis of Pancasila Application in Informatics Class Students of Medan Institute of Technology in Daily Life. Pancasila has the essence of a philosophical system in every line. The purpose of this study is to determine the application of the philosophy of Pancasila education among students of the Informatics Class of the Medan Institute of Technology. The method used in the study is a qualitative method in the form of non-test observation. The results of the study revealed that 32 out of 33 students had implemented Pancasila values in their daily lives well.Keywords : Education, Philosophy, PancasilaAbstrak : Analisis Penerapan Pancasila Di Kalangan Mahasiswa Kelas Informatika Institut Teknologi Medan Dalam Kehidupan Sehari-Hari. Pancasila memiliki hakikat sebagai sistem filsafat pada setiap silanya. Adapun tujuan dari penelitian ini untuk mengetahui penerapan filsafat pendidikan pancasila pada kalangan mahasiswa Kelas Informatika Institut Teknologi Medan. Adapun metode yang digunakan dalam penelitian ialah metode kualitatif berupa observasi non-tes. Hasil dari penelitian diketahui bahwa 32 dari 33 mahasiswa sudah menerapkan nilai-nilai pancasila dalam kehidupan sehari-hari dengan baik.Kata Kunci : Pendidikan, Filsafat, Pancasila